2015
DOI: 10.1098/rsif.2015.0737
|View full text |Cite
|
Sign up to set email alerts
|

Total ellipse of the heart valve: the impact of eccentric stent distortion on the regional dynamic deformation of pericardial tissue leaflets of a transcatheter aortic valve replacement

Abstract: Transcatheter aortic valve replacements (TAVRs) are a percutaneous alternative to surgical aortic valve replacements and are used to treat patients with aortic valve stenosis. This minimally invasive procedure relies on expansion of the TAVR stent to radially displace calcified aortic valve leaflets against the aortic root wall. However, these calcium deposits can impede the expansion of the device causing distortion of the valve stent and pericardial tissue leaflets. The objective of this study was to elucida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Sun et al 42 used FE analysis to investigate the effect of elliptical stent deployment on TAV leaflet stresses and strains, which they found to be significantly increased compared to those in the nominal cylindrical stent. These simulation results were later confirmed by in vitro results reported by Gunning et al 14 , in which elliptically deployed TAVs were shown to have increased leaflet strains compared to nominally deployed valves particularly in the commissural regions. Abbasi and Azadani 1 have shown that TAV leaflet stresses and strains increase at the commissures in the underexpanded configuration as well due to sharp bending through FE analysis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Sun et al 42 used FE analysis to investigate the effect of elliptical stent deployment on TAV leaflet stresses and strains, which they found to be significantly increased compared to those in the nominal cylindrical stent. These simulation results were later confirmed by in vitro results reported by Gunning et al 14 , in which elliptically deployed TAVs were shown to have increased leaflet strains compared to nominally deployed valves particularly in the commissural regions. Abbasi and Azadani 1 have shown that TAV leaflet stresses and strains increase at the commissures in the underexpanded configuration as well due to sharp bending through FE analysis.…”
Section: Discussionsupporting
confidence: 75%
“…TAV structural failures as early as 3 years after implantation have been cited 3, 17, 20 . Furthermore, it has been shown that poor leaflet coaptation 27, 45 will reduce the durability of bioprosthetic SAVs; thus, it follows that the durability of TAVs that exhibit poor leaflet coaptation as seen under non-optimal deployment conditions (elliptical, underexpanded, non-uniformly expanded) 14, 15, 43 , would be further reduced. Therefore, there is a critical need for more comprehensive studies on the long-term durability of TAV devices in various configurations to assess deployment strategies and provide insight for improved design.…”
Section: Introductionmentioning
confidence: 99%
“…Resolving the 3D leaflet motion would require 3D imaging and subsequent surface reconstruction. 32,33 This was beyond the scope of this work and may be topic of future investigations.…”
Section: Limitationsmentioning
confidence: 97%
“…However, this strategy may result in incomplete expansion of the transcatheter valves and thus some degree of valve leaflet—stent orifice mismatch 51. This may, in turn, cause pin-wheeling motion of leaflets during closure with ensuing increased mechanical stress 54.…”
Section: Durability Of Transcatheter Bioprosthesesmentioning
confidence: 99%